ผลของการผ่อนคลายกล้ามเนื้อแบบโพรเกรสซีฟต่อความอยากบุหรี่ในผู้ที่สูบบุหรี่ - ทัศนีย์ ลิมป์สานนท์ (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
This study is a randomized controlled trial. Data were collected from 34 cigarette refraining smokers. The sample was randomly divided into experimental group (n=17) who received progressive muscle relaxation (PMR) and the others to be in the control group (n=17) who received reading newspaper. This study used the Semi-Structured Assessment for Drug Dependence and Alcoholism (SSADDA), Penn Alcohol Craving Scale (PACS), drug-related Visual Analog Scale (VAS) and blood pressure monitoring. The demographic and cigarette use data of the two groups were compared by using chi-square test and independent-samples T test. Paired-Samples T test and Wilcoxon signed-rank test were used to compare the difference of the PACS, VAS and blood pressure before and after sessions on both groups. Non-Parametric Mann-Whitney test and ANCOVA were used to compare the difference between control and intervention groups. The research was carried out from August to November, 2012.After receiving PMR, the experimental group had lower averaged smoking craving score (PACS, VAS), stimulated, anxious, hungry, bad and systolic blood pressure than control group (P<0.05). After receiving PMR, subjects in the experimental group had lower average smoking craving score (PACS, VAS), stimulated, anxious, hungry, bad, systolic and diastolic blood pressure at post-PMR when compared to baseline (P<0.05). However, PACS, VAS and blood pressure after reading newspaper of the control group did not differ to those at baseline.